Teachers’ Contribution to Child-Friendly Schools in Grade IV Elementary School Through Anti-Bullying Activities - Hidayat, Wahyu; Wulandari, Yuni; Surbakti, Seni Sehati; Hasanah, Uswatun (Jurnal Penelitian Medan Agama, 2025)
Teachers are responsible for providing education to students at school. A teacher's responsibility extends beyond imparting knowledge to students and also to fostering positive attitudes and behaviors, fostering respect, honesty, responsibility, and so on. Therefore, schools must be able to recruit competent teachers. The forms of bullying behavior include physical bullying, verbal bullying, and mental/psychological bullying. Bullying can occur anywhere, especially in the school environment. The formation of bullying behavior itself occurs because of oppression and coercion against the victim so that the victim feels afraid and abused. So that students find it difficult to actualize themselves. So a conducive school environment can create an effective teaching and learning process for students. This research is qualitative, emphasizing the discovery and analysis of findings through descriptive analysis. Therefore, the data collection and analysis methods employed are qualitative. The unit of analysis is the object under study, which relates to the object, individual, or group as the research subject. The unit of analysis in this study is the qualitative narratives obtained from in-depth interviews with the principal, teachers, and students regarding teachers' contributions to anti-bullying activities